Acute Heart Failure Caused by Parvovirus B-19 Myocarditis Treated with Human Immunoglobulin. (30th July 2012) - Alberti, Luca; Loffi, Marco; Fragasso, Gabriele; Spoladore, Roberto; Ballarotto, Carlo; Margonato, Alberto
Abstract : We describe the case of a 42-year-old woman developing cardiogenic shock with cardiac tamponade due to an acute myo-pericarditis caused by Parvovirus B19 (PVB19), successfully treated with intravenous (iv) immunoglobulin administration.